An assessment of the natural radioactivity distribution and radiation hazard in soil samples from Qatar using high-resolution gamma-ray spectrometry. (November 2017) - Al-Sulaiti, Huda; Al Mugren, K.S.; Bradley, D.A.; Regan, P.H.; Santawamaitre, T.; Malain, D.; Habib, A.; Nasir, Tabassum; Alkhomashi, N.; Al-Dahan, N.; Al-Dosari, M.; Bukhari, S.
Abstract: We establish baseline measurements for radioactivity concentration in the soil samples collected from the Qatarian peninsula. The work focused on the naturally occurring and technically enhanced levels of radiation associated with 235, 8 U and 232 Th natural decay chains and the long-lived naturally occurring radionuclide 40 K in 129 soil samples collected across the landscape of the State of Qatar. Three radiological distribution maps showing the activity concentrations of 226 Ra, 232 Th and 40 K were constructed. Two soil samples were found to be elevated to the favour of 226 Ra concentration and significantly above the average and global values. Notably, these samples were collected from an area within an oil field (NW Dukhan). The mean values of activity concentrations of 226 Ra, 232 Th and 40 K for the full cohort of samples were found to be 17.2±1.6, 6.38±0.26 and 169±5 Bq/kg, respectively. These values lie within the expected range relative to the world average values in soil samples of 30, 35 and 400 Bq/kg, respectively. Highlights: This study aimed to establish a baseline for soil radioactivity in Qatar. The work focused on measurement of NORM levels in 129 samples using HPGe detector. The mean values lie within the range relative to the world average values. The Ac of Dukhan soil samples were elevated. The mean of D, Raeq, Hex and AEDE had all normal levels of radiation.